Reactive Oxygen Species Secreted by Leukocytes in Semen Induce Self-Expression of Interleukin-6 and Affect Sperm Quality. Issue 5 (October 2020) - Li, Xiaoping; Ni, Mengxia; Xing, Shiyu; Yu, Yi; Zhou, Yan; Yang, Shenmin; Li, Hong; Zhu, Rui; Han, Mutian
Reproductive tract inflammation is considered an important cause of male infertility. Increased leukocytes in semen can produce many reactive oxygen species (ROS), which affect sperm function. The aim of this study is to identify the main source of ROS in seminal plasma and to assess the effect of ROS on leukocytes. Semen samples ( n = 20) with leukocyte concentration >1 × 10 6 were collected from a male infertility clinic. This study mainly compares the sperm function parameters of the normal group and the semen white blood cell group >1 × 10 6 . The results identified that ROS in semen was closely related to sperm function parameters, and CD45 + leucocytes were the main source of ROS. Compared with the control group, the concentration of IL-2, IL-4, IL-6, IFN-γ, and TNF-α was higher in the experimental group. Leukocytes in semen may regulate the secretion of ROS through the mammalian target of rapamycin (mTOR) pathway. A considerable amount of ROS can upregulate the expression of IL-6 in leukocytes via the nuclear factor kappa-B (NF-kB) pathway.